ReConNet: A Tool for Modeling and Simulating with Reconfigurable Place/Transition Nets - Padberg, Julia; Ede, Marvin; Oelker, Gerhard; Hoffmann, Kathrin (Electronic Communications of the EASST, 2012)
In this contribution we present a tool for modeling and simulation with reconfigurable Petri nets. Taking the idea of algebraic graph transformations to marked Petri nets we obtain Petri nets whose net structure can be changed dynamically. The rule-based change of the net structure enables the adequate modeling of complex, dynamic structures as for example of the scenarios of the Living Place Hamburg. The tool econnet uses decorated place/transition nets that are extended by various annotations. Especially, they have transition labels that may change when the transition fires. The transformation approach is based on the well-known algebraic transformation approach, but here we use a variant, namely the cospan approach, that inverts the relation between left- and right-hand sides and interface in the rules.